The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/1040638715597724
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofMannheimia haemolyticain beef calves via nasopharyngeal culture and pulsed-field gel electrophoresis

Abstract: Abstract. Mannheimia haemolytica is a major bacterial component of bovine respiratory disease (BRD); unfortunately, very little is known about M. haemolytica transmission dynamics among cattle. Identifying potential variation in M. haemolytica populations over time and induction of nasopharyngeal colonization and subsequent shedding are 2 areas where knowledge is lacking. In our study, 2 separate loads of 20 mixed-origin, male calves were purchased through an order buyer on different dates. Deep nasopharyngeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Four calves were infected via endoscope-guided challenge with 3x10 8 CFU/mL of a field strain of M . haemolytica serotype A1 previously isolated from the lung of a bovine with BRDC [ 31 , 32 ]. Protocols for growing and administering the challenge inoculum have been previously described [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four calves were infected via endoscope-guided challenge with 3x10 8 CFU/mL of a field strain of M . haemolytica serotype A1 previously isolated from the lung of a bovine with BRDC [ 31 , 32 ]. Protocols for growing and administering the challenge inoculum have been previously described [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…haemolytica serotype A1 previously isolated from the lung of a bovine with BRDC [ 31 , 32 ]. Protocols for growing and administering the challenge inoculum have been previously described [ 31 , 32 ]. Four calves served as uninfected controls and received only PBS via endoscope-guided administration.…”
Section: Methodsmentioning
confidence: 99%
“…A test that could rapidly and accurately distinguish genotype 1 and 2 M. haemolytica could be beneficial to diagnostic laboratories and veterinary practitioners that currently identify M. haemolytica at the species level using culture. Within a single animal, M. haemolytica cultured from the nasopharynx may genetically differ from those cultured from the lung, making culture findings from nasal swabs and other antemortem clinical samples challenging to interpret (Capik et al, 2015). A test to rapidly distinguish genotypes would provide an enhanced ability to interpret M. haemolytica culture and subsequent antimicrobial susceptibility testing results from nasal swabs or other samples that contain M. haemolytica of either genotype.…”
mentioning
confidence: 99%
“…The results of this study demonstrate that the MH-challenge model successfully initiated immunological signs of disease, despite the fact that there were few observed clinical signs of disease detected following the MH challenge. Gross clinical signs of disease resulting from the challenge model were not expected as previous studies using a similar MH strain with intratracheal delivery reported that MH-challenged animals appeared clinically normal or displayed mild increases in clinical illness scores that were not different from clinically normal (Corrigan et al, 2007;Capik et al, 2015).…”
Section: Discussionmentioning
confidence: 81%